Schizotypy and specificity of negative emotions on an emotional Stroop paradigm in the general population. (30th May 2016) - Yaffe, Beril; Walder, Deborah J.
Abstract: Attentional-interference using emotional Stroop tasks (ESTs) is greater among individuals in the general population with positive (versus negative) schizotypal traits; specifically in response to negatively (versus positively) valenced words, potentially capturing threat-sensitivity. Variability in attentional-interference as a function of subcategories of negatively valenced words (and in relation to schizotypal traits) remains underexplored in EST studies. We examined attentional-interference across negative word subcategories (fear/anger/sadness/disgust), and in relation to positive schizotypy, among non-clinical individuals in the general population reporting varying degrees of schizotypal traits. As hypothesized, performance differed across word subcategories, though the pattern varied from expectation. Attentional-interference was greater for fear and sadness compared to anger; and analogous for fear, disgust, and sadness. In the high schizotypy group, positive schizotypal traits were directly associated with attentional-interference to disgust. Attentional-interference was comparable between high- and low-positive schizotypy. Results suggest negative emotion subcategories may differentially reflect threat-sensitivity. Disgust-sensitivity may be particularly salient in (non-clinical) positive schizotypy. Findings have implications for understanding negative emotion specificity and variability in stimulus presentation modality when studying threat-related attentional-interference. Finally, disgust-related attentional-interference may serve as a cognitive correlate of (non-clinical) positive schizotypy. Expanding this research to prodromal populations will help explore disgust-related attentional-interference as a potential cognitive marker of positive symptoms. Highlights: Attention is adversely impacted by negative emotion (attentional interference) in psychosis and contributes to positive psychotic symptoms. We examined attentional interference (using an emotional Stroop) across negative word subcategories and schizotypal traits in the general population. Results suggest negative emotions may be differentially linked with threat-sensitivity; and with disgust-sensitivity in positive schizotypy. Negative emotion specificity and variability in stimulus modality are important when studying threat-related attentional interference. Disgust related attentional interference may be a cognitive correlate of positive schizotypy and serve as a relevant marker of psychosis risk.